Basal skull fractures are associated with mortality in pediatric severe traumatic brain injury. Issue 6 (June 2015) - Alhelali, Ibrahim; Stewart, Tanya Charyk; Foster, Jennifer; Alharfi, Ibrahim M.; Ranger, Adrianna; Daoud, Hani; Fraser, Douglas D.
<x xml:space="preserve">Abstract</x> BACKGROUND Basal skull fractures (BSFs) are caused by blunt force trauma, occurring in the temporal, occipital, sphenoid, and/or ethmoid bones. In pediatric severe traumatic brain injury (sTBI), there is a paucity of data on BSFs. Our goal was to investigate the BSF prevalence, anatomy, and association with short-term outcomes in pediatric sTBI. METHODS We retrospectively reviewed all severely injured (Injury Severity Score ≥12) pediatric patients (aged <18 years) admitted to our hospital after experiencing an sTBI (Glasgow Coma Scale score ⩽8 and head Abbreviated Injury Scale score ≥4). Neuroimaging for all sTBI patients was reviewed for skull fractures. Data were analyzed with both univariate and multivariate techniques. RESULTS Of the 180 patients with sTBI, 47 had BSFs for a prevalence of 26% (69 BSFs in total; 16 sTBI patients had ≥2 BSFs). The squamous temporal bone was fractured most frequently (n=30/47 sTBI patients with BSFs). Patients with BSFs were heavier and had more facial injuries than those without (p < 0.05) but were similar in all other admission demographics, injury profiles, and clinical characteristics. Cerebrospinal fluid leak was found in 32% (n = 15 of 47) of BSF patients (otorrhea, n = 12; rhinorrhea, n = 1; otorrhea/rhinorrhea, n = 2; p < 0.001). Mortality, acute central diabetes insipidus, and fewer ventilator-free days were associated with BSFs (p < 0.005), whereas in sTBI survivors, BSFs were associated with longer lengths of stay (p < 0.05). Multiple logistic regression showed that BSFs were positively associated with the presence of subarachnoid hemorrhage (odds ratio [OR], 4.00; p = 0.001), contusion (OR, 2.48; p = 0.029), herniation (OR, 3.40; p = 0.037), and cerebral edema (OR, 2.30; p = 0.047) but negatively associated with diffuse axonal injury (OR, 0.20; p = 0.003). BSFs and mortality were strongly associated (OR, 6.87; p = 0.019). CONCLUSION BSFs occurred in 26% of pediatric sTBI patients. The temporal bone was fractured in two thirds of sTBI patients with BSFs, and one third was associated with cerebrospinal fluid leaks. BSFs represent a significant linear blunt force and are independent predictors of mortality. LEVEL OF EVIDENCE Prognostic and epidemiologic study, level III.